Thermal behavior studies of solid state compounds of 4-dimethylaminocinnamylidenepyruvate with alkali earth metals, except beryllium and radium - SCHNITZLER, Egon; COSTA, Wilson; MELIOS, Cristo Bladimiros [UNESP]; LELES, Maria Ines Gonçalves; Ionashiro, Massao [UNESP] (Editora Unesp, 2000)
Foram preparados no estado sólido, compostos de fórmula geral M(DMCP)2 nH2O, em que M representa Mg, Ca, Sr, Ba; DMCP é 4-dimetilaminocinamalpiruvato e n = 1, exceto para o Ca onde n = 2,5. Na caracterização, bem como no estudo da decomposição térmica desses compostos, foram utilizados a termogravimetria, termogravimetria derivada (TG, DTG), calorimetria exploratória diferencial (DSC), difração de raios-X pelo método do pó e complexometria.

Solid state compounds of general formula M(DMCP)2.nH2O, where M represents Mg, Ca, Sr, Ba, and DMCP is 4-dimethylaminocinnamylidenepyruvate, and n = 1, except for Ca, where n = 2.5, have been prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal decomposition of these compounds.
Estudo do comportamento térmico dos 4-dimetilaminocinamalpiruvato de metais alcalino terrosos, exceto berílio e rádio, no estado sólido
Keywords: 4-dimetilaminocinamalpiruvato; Metais alcalino-terrosos; Decomposição térmica; 4-Dimethylaminocinnamylidenepyruvate; Alkali earth metals; Thermal decomposition